Fast Track or Failure: A Study of the Completion Rates of Graduate Students in Economics - Jan C. van Ours; Geert Ridder (Institute for the Study of Labor (IZA), 2000)
This paper presents an analysis of the failure and completion rates of graduate students in economics at three universities in The Netherlands. We find that an indicator of the research productivity of the supervisor is an important determinant of the completion and dropout rates. However, this effect seems due to the fact that supervisors with a good research record attract and select better students. There is no evidence of an independent effect of having a supervisor who is an active researcher.
Keywords: C41; I21; 330; Duration analysis; education; graduate program; Wirtschaftsstudium; Dauer; Abbrecher; Niederlande